Intralinguistic Motivation for Pluralism about Truth - Joseph ULATOWSKI (Studia Universitatis Babeș-Bolyai. Philosophia, 2024)
Critics of the scope problem that motivates pluralism about truth have argued that it is a pseudo-problem. If the criticism is correct, then truth pluralism is left unmotivated and potentially bankrupt. In this paper, I argue that closely related to the scope problem is another problem, which I call “the scalar problem.” If the property of truth is sensitive to how an agent expresses the truth predicate within a single linguistic discourse and different agents or groups of agents express truth differently within that discourse, then there are different ways of being true within the same linguistic discourse. Given this possibility, even if the scope problem fails, truth pluralism remains fully motivated.